Investigation of the Effect of Cognitive Behavioral and Physical Development Levels on the Multiple Intelligence of University Students - Gülle, Mahmut (Asian Journal of Education and Training, 2019)
In this study, it was designed to examine the multiple intelligence levels, cognitive, physical and affective levels of the faculty students studying at Hatay Mustafa Kemal University. The population of the study was composed of students studying at Hatay Mustafa Kemal University in 2018 - 2019 academic year. The sample included 1142 students (Male = 603, Female = 539) chosen by random sampling method. In the study, “Cognitive, Behavioral and Physical” scale developed by Schembre et al. (2015) adapted to Turkish by Eskiler et al. (2016) and “Multiple Intelligence” scale developed by Gardner (1990) adapted to Turkish by Demirtas and Duran (2007) were used as a data collection tool. In order to test the hypotheses of the study, t-test (Mann-Whitney U test) and analysis of variance in multiple comparisons (Kruskal Wallis-H test) were performed in addition to descriptive statistics such as arithmetic mean, standard deviation, frequency/percentage, normal distribution test, (Kolmogorov-Smirnov test). As a result of the study, it was found that there was a significant difference between the participants’ cognitive behavioral physical activity and multiple intelligence levels in relation to gender, income status and sporting variables.